2019
DOI: 10.21512/bbr.v10i3.5712
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Automobile Sales in Indonesia: An Empirical Study in 1986-2016

Abstract: The aim of this research was to study the determinants of automobile sales in Indonesia. The automobile sales were the sales of car and motorcycle during 1986-2016. The research focused on five macroeconomics variables (exchange rate, Gross Domestic Product (GDP), growth of GDP, inflation, and interest rate). The total sample was 30 years of automobile sales in Indonesia. The researcher used the regression method with Statistical Package for the Social Sciences (SPSS) to test the research model. For a few vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…408 respondents in Turkey are surveyed based on gender, age, monthly income, family size, driving license type, and fuel type, determining their influence on light commercial car demand. Johan (2019) studies the macroeconomic determinants of car and motorcycle sales in Indonesia. It is found that the gross domestic product and changes in a gross domestic product have a significant influence on car and motorcycle sales in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…408 respondents in Turkey are surveyed based on gender, age, monthly income, family size, driving license type, and fuel type, determining their influence on light commercial car demand. Johan (2019) studies the macroeconomic determinants of car and motorcycle sales in Indonesia. It is found that the gross domestic product and changes in a gross domestic product have a significant influence on car and motorcycle sales in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The automotive sector is the critical contributor to the country's budget on the income side. However, the sales of automotive are unpredictable from year to year, which consequently affect the budget income of the country as well as the realization of the annual government budget (Johan, 2019). Therefore, the government needs to be able to predict the determinant of automotive sales in their country.…”
Section: Introductionmentioning
confidence: 99%
“…The financial services institution transfers funding from the public to businesses via credit. This financing also stimulates the consumption sectors, as shown through motor vehicle financing in emerging markets (Johan, 2019) and other consumables such as appliances. Entrepreneurs are crucial in creating productivity that leads to economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional business models are gradually being abandoned and turning to digitization, which many see as the business landscape of the future. In his paper, Korbel (2016) in [2] states that machines and technology substitute conventional [3] states that innovation in the future will always be related to big-data analysis, which is supported by technology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, macroeconomic indicators represent the business and sales potential [16]. The impact of economic growth and gross domestic product to sales of cars and motorbikes [3]. The population will reflect the number of potential customers.…”
Section: Introductionmentioning
confidence: 99%